Transesophageal echocardiography guidance for percutaneous closure of PFO and a new method to improve the diagnosis and safety during the procedures - Luo, Limin; Xie, Zehan; Wu, Qiaoyan; Liu, Qiang; Hou, Huiping; Wang, Yongshi; Shu, Xianhong (Frontiers in Cardiovascular Medicine, 2024)
Purpose Percutaneous patent foramen ovale (PFO) closure is becoming more and more common for the treatment or prevention of PFO-associated right-to-left shunt (RLS). This study aims to investigate the value of transesophageal echocardiography (TEE) in percutaneous PFO closure, and to explore a new method that can improve intraoperative diagnosis and surgical safety. Materials and methods Based on our inclusion and exclusion criteria, we enrolled 73 patients between 16 and 70 years old (average age 43.25 ± 14.87 years) who underwent percutaneous PFO closure at the Department of Cardiac Surgery, Zhongshan Hospital (Xiamen), Fudan University, from January 2022 to December 2023. Out of the 73 enrolled patients, there were 28 males (38.36%) and 45 females (61.64%), 29 migraine patients (39.73%), 14 patients (19.19%) with headache and dizziness, 14 patients (19.18%) with a history of cerebral infarction (CI), and 25 patients (34.25%) with CI, lacunar infarction or ischemic focus on magnetic resonance imaging (MRI). All patients received routine transthoracic echocardiography (TTE) and agitated saline contrast echocardiography (ASCE) before operations. Percutaneous closure of PFO was completed under the guidance of TEE. In 12 patients, the method of “injection of heparinized sterile saline through the delivery sheath” was used to observe their RLS, and the anatomical characteristics of the PFO according to the shunt path were monitored and evaluated. This method was also applied to some patients to guide the conveyor to pass through the foramen ovale (FO) channel safely and effectively, thereby improving the success rate of PFO closure. Results The application of TEE during the procedure of percutaneous PFO closure, including preoperative evaluation, intraoperative guidance, and postoperative reevaluation, can offer further details about the anatomical and shunt characteristics of PFO, improve the diagnosis rate, and confirm the safety of the surgical path. It ensures the safety and reliability of the whole operation, greatly improving the success rate and reducing postoperative complications. Conclusions TEE guidance of percutaneous PFO closure has the advantages of minimal trauma, no radiation and real-time visualization, while injecting heparinized sterile saline through the delivery sheath is safer and more effective in improving the success rate and reducing postoperative complications.